Fear of fear in Job 4:14 - Pinker, Aron (Biblische Notizen, 2006)
I argue that the standard interpretations of Job 4:14 that assume פחד = “fear” andקרה = קרא “happen, occur” do not provide a natural, unforced, textually and contextually consistent understanding of the text. It is suggested that in Job 4:14 פחד is a numen, קרא is “call,” and the verse means “God called me, and a trembling, and quaking shook my bones.”